Sequence homologies in the 5' regions of four Drosophila heat-shock genes. - Holmgren, R (1981)
We report nucleotide sequences of the regions surrounding the 5' ends of the genes for Drosophila melanogaster heat-shock proteins hsp83, hsp68, and hsp26, located at chromosome positions 63BC, 95D, and 67B, respectively. As in other eukaryotic genes, the sequence T-A-T-A-A-A-A-T occurs about 30 nucleotides upstream from the sites of mRNA initiation. Three additional sequence homologies and a dyad symmetry were noted at approximately corresponding locations in the three genes and in the gene for another heat-shock protein, hsp70. We also found an intron near the 5' end of the hsp83 gene, with sequences at its boundaries typical of splice sites found in other organisms.